The response of coastal macrobenthic food-web structure to seasonal and regional variability in organic matter properties. (December 2021) - Szczepanek, Marta; Silberberger, Marc J.; Koziorowska-Makuch, Katarzyna; Nobili, Edoardo; Kędra, Monika
Highlights: Spatial and temporal variability of benthic isotopic niches were investigated. Food web structure follows the patterns of organic matter quantity and quality. Higher organic matter supply supports food web diversity and benthic carnivory. Spatio-temporal food-web structure is a good indicator of ecosystem function. Abstract: The quantity and quality of organic matter (OM) available for macrobenthos vary on temporal and spatial scale, especially in coastal areas, where the seafloor is supplied by both seasonal pulses of primary production and terrestrial carbon transported by rivers. Human-induced environmental changes will alter OM transport to the seafloor, thus, it is of crucial importance to recognize the impacts of spatio-temporal OM variability on macrobenthic food webs. In this study, the seasonal variability of quantity and quality of OM and its effect on benthic food-web structure were studied at four locations along the southern coast of the Baltic Sea, characterized by similar species pools but different environmental settings and various scales of anthropogenic and riverine influence. Our study shows that temporal changes in the isotopic niche (δ 13 C and δ 15 N) of benthic invertebrates follow the patterns of quantity and quality of OM related to seasonal changes of pelagic primary production, riverine discharge of terrestrial OM and the input of anthropogenically enriched sources. In the semi-enclosed bay, exposed to intensive summer blooms, all feeding groups expressed lower δ 15 N values in autumn, suggesting the incorporation of δ 15 N-depleted cyanobacteria. At a location supplied by a higher proportion of OM from allochthonous sources (riverine discharge), omnivores occupied higher trophic levels, probably due to a higher abundance of meiobenthic prey. In contrast, at the open Polish coast, where the main food supply occurs during diatom spring bloom, the isotopic niche of omnivorous species showed much higher seasonal variability, underlining the importance of food availability for food-web diversity. Quick adaptation of benthic food-web structure to seasonal variations in OM properties and its modification by local conditions may indicate high plasticity of species feeding behavior that suggests a high capacity of benthic communities to mitigate ongoing changes in the marine environment, at least within the range observed today. Our results confirm that combination of spatial and temporal scales in sampling of the food-web structure is a good indicator of the ecosystem stability and function.